Menghancurkan Kepalsuan (Studi Tentang Tindak Pidana Pemalsuan Dan Problema Penerapannya) - Zulfa, Eva (Jurnal Hukum & Pembangunan, 2018)
The development of the falsification of letter or document falcification has in essence undergone tremendous progress attributed to the qualification and types of documents, the various provisions and types of documents, the various provisions of rules and regulation and the interpretation of its. The evidiantary system associated with e-document is highly developed with several of form. This development makes the interpretation of the elements in the formulation of the article that has been the various provisions of the article 263, article 264 or article 266 KUHP very developed. The calculation of the expiration of prosecution which of the become a part of legal implementation problem related to the froud. Hence, the study of the interpretation element of crime in various judgement of Hoge Raad, the decition of the Supreme Court and The Constitutional Court Ruling make good comparations in view of the development of the understanding and adaptation of the provisions of legislation with the development of the cases in its application.